Anti-tumor effects of shikonin derivatives on human medullary thyroid carcinoma cells. Issue 2 (February 2017) - Hasenoehrl, Carina; Schwach, Gert; Ghaffari-Tabrizi-Wizsy, Nassim; Fuchs, Robert; Kretschmer, Nadine; Bauer, Rudolf; Pfragner, Roswitha
Abstract : New treatment options are needed for medullary thyroid carcinoma (MTC), a highly metastasizing neuroendocrine tumor that is resistant to standard radiotherapy and chemotherapy. We show that the following shikonin derivatives inhibit cell proliferation and cell viability of the MTC cell line TT: acetylshikonin, β, β-dimethylacrylshikonin, shikonin and a petroleum ether extract of the roots of Onosma paniculata containing several shikonin derivatives. The unsubstituted shikonin derivative was found to be the most effective compound with an IC50 of 1.1 µM. The cell viability of normal human skin fibroblasts, however, was not affected by the tested substances, indicating that shikonin derivatives might be selectively toxic for cancer cells. We further report that migration and invasion of TT cells were inhibited at non-toxic concentrations. Finally, shikonin was tested in vivo using the chick chorioallantoic membrane assay, where it significantly reduced tumor growth by inhibiting cell proliferation and inducing apoptosis. In summary, our results suggest that shikonin derivatives have the potential for the treatment of medullary thyroid carcinomas.